Body mass index mortality paradox in chronic kidney disease patients with suspected cardiac chest pain. Issue 1 (1st January 2017) - O'Driscoll, Jamie M; Slee, Adrian D; Sharma, Rajan
Abstract: Background: Chronic kidney disease (CKD) is a silent clinical condition associated with adverse comorbidity and high cardiovascular disease (CVD) risk. An inverse relationship with body mass index (BMI) and mortality has been demonstrated in hemodialysis patients. However, it is unclear if this risk‐factor paradox is evident in non‐dialysis CKD patients. The aims of this study were to explore the relationship between, nutritional status, markers of inflammation, autonomic and cardiac function with BMI. Longitudinal follow‐up explored the relationship between BMI and all‐cause mortality. Methods: 211‐consecutive CKD patients referred for dobutamine stress echocardiography to detect or exclude myocardial ischemia were recruited. BMI, albumin, C‐reactive protein (CRP) and haemoglobin (Hb) were recorded as markers of nutritional and inflammatory status. Left ventricular ejection fraction (LVEF) and heart rate variability (HRV) as an indicator of cardiac function was recorded. All subjects were followed prospectively until November 2014 and study end‐point was all‐cause mortality. Results: BMI was inversely associated with CKD status. After covariate adjustment, this association remained. During a mean follow‐up period of 3.3±0.9 years there were 35 deaths (17%). BMI was inversely associated with all‐cause mortality (HR 0.81, 95% CI 0.71–0.9). Other important independent predictors of mortality were heart rate variability (HR 0.98, 95% CI 0.97–0.99), myocardial ischemia (HR 1.37, 95% CI 1.17–1.81), and albumin (HR 0.86, 95% CI 0.81–0.92). Conclusions: The presence of a BMI paradox exists in non‐dialysis CKD patients. This risk‐factor paradox was an independent predictor of all‐cause mortality and may have significant clinical implications relevant to screening, assessment and treatment and requires further study.